Pelatihan Penguatan Literasi dan Numerasi pada Guru-Guru di SMP Tunas Bangsa Kabupaten Lampung Tengah - Fitri daryanti; Dwitya Juwita; Goesthy Ayu Mariana Devi Lestari; Nabila Kurnia Adzan (Nuwo Abdimas, 2023)
Strengthening Literacy and Numeracy is very important to do, to achieve learning goals. Efforts to improve literacy and numeracy are carried out starting with the teacher. The use of media based on the surrounding environment, strategic learning, making teaching materials and materials needs to be improved. The purpose of this service activity is to increase the literacy and numeracy of teachers in the 3T area as one of the school targets in the Teaching Campus program. This activity uses the method of discussion and question and answer, the results of this activity show that the new teacher understands the material and implements the teaching material using literacy and numeracy. The steps taken by the service team are starting with compiling materials, strategies, media that can be used to improve Literacy and Numeracy through appropriate environment-based learning resources for student Literacy and Numeracy activities; using the right strategy to build student literacy and student numeracy. This was only understood by the teacher when he received training. It is important to conduct outreach and training to strengthen literacy and numeracy for teachers in schools in the 3T areas.